The Difference of Hypoxia Inducible Factor 2α mRNA Expression in High-Grade and Low-Grade Glioma Tissue - Bagus Ramasha Amangku; Syaiful Ichwan; Septelia Inawati Wanandi; Novi Silvia Hardiany (Indonesian Journal of Cancer, 2019)
Background: HIF-2α is a transcription factor in hypoxic condition, and high expression levels of it correlate with the concepts of metastasis, therapy opposition and reduced quality of prognosis in various forms of cancerous growth. Due to the exceedingly infiltrative ability of brain glioma cells, gliomas cannot be completely deteriorated with surgery and the relapse rate is high. This study goal to identify the relative expression of HIF-2α gene in the direction of glioma malignancy and its classification. Methods: Specimens used in this research comprise of 20 glioma samples obtained from glioma patients in Cipto Mangunkusumo Hospital. Relative expression of HIF-2α was measured by utilizing quantitative Real Time-Polymerase Chain Reaction (RT-PCR). Cycle threshold (CT) values were achieved correlated with the amplified DNA, and then the relative expression was attained by using Livak method of calculation. Results: The results produced a greater average of relative expression of HIF-2α in the grade III and IV types (18.64; n=7) rather than in the lower grades (5.68; n=13). However, the data is statistically inconsequential. Conclusions: High-grade glioma tends to express HIF-2α mRNA higher compared to the lower grade. Therefore, it is possible to use HIF-2α as a prognostic marker for glioma- diagnosed patients, although additional experiments need to be performed to strengthen these facts.